Importance of handwriting: how Montessori didactic materials support handwriting - McFarland, Erin (My University, 2015)
In this high-tech age, handwriting in modern society is at a decline; this is true in education as well. The Common Core ignores the importance of handwriting; Montessori curriculum highlights the importance of writing skills. Handwriting has been shown to boost brainpower, aid in memory, improve motor skills as well as become a gateway to reading. This study was done to discover what classroom strategies support the development of handwriting in a mixed age class and to gain insight into what benefits result for the child in learning this skill. This action research project was conducted in a Montessori preschool in a Midwest city area. Twenty preschool participants ages 2 1/2 to 5 years old were studied and evaluated over an 8-month period of time. The Montessori didactic materials, which have been used in Montessori classrooms for over a hundred years, were used to teach handwriting. In addition, writing was added to other subject areas to further encourage writing work. Observation, photographs, small-group presentations, student and parent interviews and handwriting samples were used to compile data. The results were positive. Students grew in handwriting ability and they chose handwriting works on their own. The Montessori materials proved effective; however they were even more effective when combined with a whole Montessori approach. This includes the preliminary works done in Practical Life and Sensorial to strengthen the hands and develop concentration and coordination. Parents also noticed a change in their children's handwriting and believed that Montessori materials were beneficial. As modern education moves away from handwriting instruction this study shows that handwriting is still essential and necessary for the whole education of the child and can be readily integrated into an early childhood curriculum.
Plan B Paper. 2015. Master of Science in Education- Montessori--University of Wisconsin-River Falls. Teacher Education Department. 55 leaves. Includes bibliographical references (leaves 48-49).
Keywords: Penmanship--Study and teaching; Montessori method of education